Human teeth versus bovine teeth: cutting effectiviness of diamond burs - Fais, Laiza Maria Grassi [UNESP]; Marcelo, Caroline Canhizares [UNESP]; Guaglianoni, Dalton Geraldo [UNESP]; Pinelli, Lígia Antunes Pereira [UNESP]; Silva, Regina Helena Barbosa Tavares da [UNESP] (My University, 2010)
Aim: In this study, a mass-loss method was used to verify whether bovine enamel has the same wear pattern as human enamel in cutting efficiency tests of diamond burs. Methods: Seventy-two teeth were used: 36 human molars (HT) and 36 bovine mandibular central incisors (BT). The enamel of the teeth was cut using diamond bur #1092 attached to a high-speed handpiece under controlled pressure (50-80 g). Each bur (n=12) cut for a total of 72 min, divided into 6 periods of 12 min each (12-min, 24-min, 36-min, 48-min, 60-min, and 72-min). The amount of enamel removed was determined by the difference between pre- and post-cut tooth masses. Results: The mean amounts (g) of enamel removed were: HT- 12-min=0.11; 24-min=0.12; 36-min=0.11; 48-min=0.11; 60-min=0.10; 72-min=0.12; BT- 12-min=0.12; 24-min=0.15; 36-min=0.15; 48- min=0.13; 60-min=0.16; 72-min=0.14. Data were analyzed using ANOVA followed by Tukey’s test, and the results showed statistically significant differences between human and bovine teeth (p<0.001) and among the cutting periods (p<0.001).Conclusions: It was concluded that the cutting efficiency of the burs was different between the tested substrates, and that bovine enamel underwent greater mass loss than did human enamel.
Keywords: Teeth; Dental enamel; Cattle; Efficiency; Diamond